Advances in 3D Image and Graphics Representation, Analysis, Computing and Information Technology Algorithms and Applications, Proceedings of IC3DIT 2019, Volume 2 /: Algorithms and Applications, Proceedings of IC3DIT 2019, Volume 2. (2020) - Unknown
No abstract available